Ancient Chinese thought, modern Chinese power - Yan, Xuetong (Princeton-China series., 2013)
The rise of China could be the most important political development of the twenty-first century. What will China look like in the future? What should it look like? And what will China's rise mean for the rest of world? This book, written by China's most influential foreign policy thinker, sets out a vision for the coming decades from China's point of view. In the West, Yan Xuetong is often regarded as a hawkish policy advisor and enemy of liberal internationalists. But a very different picture emerges from this book, as Yan examines the lessons of ancient Chinese political thought for.